The role of Russian volunteers in the collapse of the international legion in the South African War - Gorelik, Boris (Scientia Militaria - South African Journal of Military Studies, 2021)
The establishment of an international legion by General Georges de Villebois-Mareuil in March 1900 was the most ambitious attempt to coordinate the activities of foreign volunteer units within a single formation during the South African War. On the general’s death (5 April 1900), De Villebois’s Russian deputy and successor, Lieutenant Colonel Yevgeny Maximov, lost control of the legion. As a hierarchical formation, it survived De Villebois by only two weeks. Given Maximov’s ample experience in conventional and unconventional warfare, and the accolades that he later won from the republican political and military leadership, including the rank of general, the legionnaires’ opposition to him appears to be unjustified. Accounting for the discrepancy between historians’ perceptions of Maximov and his lack of success in controlling the legion is based on a premise that legionnaires had compelling reasons to reject his authority. Maximov had come to Africa ostensibly as a journalist. He was yet to earn the respect of his subordinates because he had not seen action in the South African War. In subsequent weeks, having resigned from his post in the legion, he distinguished himself in the engagement at Tobaberg as the leader of the Dutch corps. By then, Maximov had the ‘moral authority’ to command an international unit, but his poor health prevented him from carrying on fighting. Unlike De Villebois, who was supported by like-minded French lieutenants, Maximov could not rely on his compatriots. Instead of endorsing his claim to leadership, the Russian corps refused to join the legion while he was in charge, and intentionally discredited him. In the power vacuum after De Villebois’s death, the legion collapsed, and a chance to transform the emerging alliance of foreign volunteer units into a formidable force was missed.